The Consideration and Positive Affirmation: A Resource for the Psychotherapist - Castaño Rodríguez, Melissa (2024)
Consideration and positive affirmation is classified by the American Psychiatric Association (APA) as one of the most effective therapeutic skills in the clinical area. Therefore, the present research aimed to understand the way in which positive regard and affirmation unfolds: its scope and challenges in clinical practice in two psychotherapists of the clinical specialization; emphasis is placed on psychotherapy with children and adolescents.  A qualitative case study methodology was implemented; for this purpose, recordings of the first four intervention sessions of two psychotherapists were used. For the analysis of this material, an observation instrument was constructed and validated by three expert researchers. For the analysis of the information, discussion sessions were held. The results show how the psychotherapists, making use of this resource, generated in the clients: openness, adherence, and perceptions of feeling valued.